Edukasi Anti-Korupsi Dalam Lingkungan Sekolah: Membangun Integritas Sejak Dini - Dea Kristiani Hutasoit; Aisyah Arianti; Alda Azzahra Fadila; Khofifa Hera Wenzana; Lia Wildah Hasanah; Putri Hermaisya Harahap; Hanina Nafilah Lukman; Melda Novitasari; Sapna Maulini Rezeki Hasibuan; Sintya Rindi Utami; Marisa Kemala Rozi (International Forum of Researchers and Lecturers, 2025)
Anti-corruption education is a strategic effort in building a young generation with integrity. This study aims to analyze the effectiveness of anti-corruption education programs in schools in instilling the values of honesty, responsibility, and justice in students. Through the [research method] method, it was found that anti-corruption education programs that integrate moral values into the curriculum can increase students' awareness of the dangers of corruption and encourage anti-corruption behavior. Awareness and understanding of corruption are crucial to be introduced early on. Therefore, instilling anti-corruption values in schools is urgent to be conveyed and developed for students. Integrity is one of the character values that needs to be instilled from an early age. To form this integrity, as agents of change, we feel called to conduct socialization regarding the importance of instilling the character value of integrity, in order to create a generation that is anti-corruption since childhood.